Sejarah, Kurikulum dan Pembelajaran Pada Kuttab: Kajian Literatur Sistematis Tahun 2013-2023 - Hamidulloh Ibda; Dian Marta Wijayanti (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
There is much literature on kuttab but little focus on the history and development, curriculum, and learning in kuttab using a systematic literature review method. This research method applies a systematic literature review and PRISMA protocol. Qualitative data analysis was assisted by the Publish or Perish 7, VOSviewer, and NVIVO 12 Plus applications. The results of searching for articles on Scopus and Google Scholar through the Publish or Perish 7 application were 4,000. Then the articles were filtered according to compatible themes into 58 articles. The 58 articles were analyzed according to the specified topics through the NVIVO 12 Plus application, and the results were described according to the research questions. The findings of this article explain that kuttab existed before Islam and developed during the classical period (650-1250 AD). The development of kuttab reached the Middle East, and in the Nusantara, there was a kuttab during the Siak Sri Inderapura Sultanate (1723-1946). In 2012, Kuttab Al-Fatih developed, which already had 34 branches, and other kuttabs with variants of names, curricula, ideology, and learning management. The kuttab curriculum in the classical period was generally divided into the tawhid (faith) curriculum and the Quran curriculum. The learning materials of kuttab before Islam came were only reading and writing. When Islam came, the kuttab curriculum added Quranic material, Islam, Nahwu, Sharaf, prayer, arithmetic, and others. Kuttab Al-Fatih curriculum in Indonesia applies the faith curriculum and the Quran curriculum. Classical kuttab learning contains faith and Quranic material by applying discussion methods, parables, memorization, discussion, stories, and others. Since 2012, kuttab has developed in Indonesia with learning according to the Kuttab Awal and Kuttab Qanuni levels.